Search for the Standard Model Higgs boson in e+e- collisions at √s = 161, 170 and 172 GeV - BARATE, R.; et al. (Institutional Knowledge at Singapore Management University, 1997)
The reaction e+ e ! HZ is used to search for the Standard Model Higgs boson. The data sample consists of integrated luminosities of 10:9 pb1 , 1:1 pb1 , and 9:5 pb1 collected by the ALEPH experiment at LEP during 1996, at centre-of-mass energies of 161, 170 and 172 GeV, respectively. No candidate events were found, in agreement with the expected background of 0.84 events from all Standard Model processes. This search results in a 95% C.L. lower limit on the Higgs boson mass of 69:4 GeV=c2 . When combined with earlier ALEPH searches performed at energies at and around the Z peak, this limit increases to 70:7 GeV=